Relationship between quality of life and resilience among sport-active Singaporean youth - Chia Michael; Lee Marcus (Physical Education of Students, 2015)
Purpose : The study examines the relationship between paediatric quality of life (PEDSQL) and resilience, measured by the Singapore Youth Resilience Scale (SYRESS) among sport-active youth transiting from primary to secondary school education in Singapore. Method : The participants were 137 student-athletes aged 12.7+-0.3 years, height 156.0+-12.9 cm, and body mass 46.4+-10.2kg. PEDsQL and SYRESS questionnaires were administered at the start of the academic year and repeated again six months later. Results : Total health (PEDsQL) scores were significantly greater at baseline than when measured six months later (77.3+-11.9 vs 72.1+-11.8; p<0.05) but there was no significant change in the SYRESS score (198.2+-25.3 vs 194.0+-27.4; p>0.05). Total health in PEDsQL was significantly correlated to SYRESS scores at both time points (Baseline r s=0.61,p<0.01; baseline plus 6 months r s=0.58, p<0.01). Conclusions : The results reflect a linkage between student's resilience and PedsQL outcomes. Student-athletes perceived the transition from primary to secondary school to be a difficult period and sport-active youth are a unique population compared to normal school going youth.